IMPLEMENTASI BAURAN PEMASARAN (MARKETING MIX 7P) DALAM MENINGKATKAN PESERTA DIDIK BARU PADA MADRASAH - Wirdatul Hasanah; Titin Nurhidayati (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study aims to determine the implementation of the marketing mix (7P marketing mix) in increasing new student enrollment at MA Plus Nurul Huda Al-Habibi. The increasing competition among educational institutions requires madrasahs to implement effective marketing strategies to attract public interest. The 7P marketing mix consisting of product, price, place, promotion, people, process, and physical evidence is used as an educational marketing strategy to increase the number of new students. This research employed a qualitative approach with a case study design. Data collection techniques included observation, interviews, and documentation. The data sources were obtained from the headmaster, teachers, new student admission committee, and parents. Data analysis techniques were carried out through data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the 7P marketing mix at MA Plus Nurul Huda Al-Habibi was carried out through the provision of superior Islamic-based educational programs, affordable tuition fees, strategic school location, promotion through social media and community activities, competent educators, good administrative services, and adequate facilities and infrastructure. The implementation of these strategies has proven effective in increasing public interest and the number of new student enrollments each year.